Analisis Kinerja Serta Kondisi Keuangan Pemerintah Daerah Kota Sungai Penuh pada Periode Tahun Anggaran 2017-2023 - Cherlita Anjani; Iskandar Sam; Rahayu Rahayu (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study analyzes the financial performance and condition of the Sungai Penuh City Government from 2017 to 2023. Financial performance is measured using key ratios such as independence, effectiveness, efficiency, activity, growth, and solvency. Financial condition is assessed through the Brown Model (10-Point Test). Using a descriptive quantitative approach, the research is based on secondary data from APBD realization reports. The results show fluctuating performance, with high fiscal dependence on central government transfers and inconsistent growth in PAD and spending efficiency. The city's financial condition is categorized as moderate, with solvency as a critical concern. Supported by legitimacy and signaling theories, the study emphasizes the importance of transparency and financial strategy to build public trust and improve regional fiscal health.